(untitled) (Research, Society and Development, 2023)
As is customary in mycorrhizae, the interaction between plant and dark septate endophytic (DSE) fungi can result in physiological changes in the host plant, which are still poorly understood. This study aimed to evaluate the physiological changes in tomato plants colonized by DSE fungi. Four DSE isolates previously identified through ITS phylogeny were inoculated on tomato seeds and compared to non-inoculated plants (control). Kinetic parameters (Vmax and Km) were calculated measuring the nitrate content in the nutrient solution. The contents of NO3–N, NH4+-N, amino-N, soluble sugars in the root, petiole, stem and leaf, and the contents of macronutrients in the shoot were determined. The plants inoculated with A101 and A105 exhibited (i) significant increases in the soluble sugar contents; (ii) increases in the contents of P, K, Mg and S; and (iii) increased dry biomass compared to control. The A103 inoculation was antagonistic when compared to the other treatments, leading to a higher influx of NO3–N in the plants, resulting in a higher amino-N and the lower soluble sugar content in the shoot. The physiological parameters of tomato varied depending on the inoculation, and the changes ranged from positive to negative depending on each isolate involved in the interaction.